The clinical relevance of heme detoxification by the macrophage heme oxygenase system - Yeudall, Scott; Upchurch, Clint M.; Leitinger, Norbert (Frontiers in Immunology, 2024)
Heme degradation by the heme oxygenase (HMOX) family of enzymes is critical for maintaining homeostasis and limiting heme-induced tissue damage. Macrophages express HMOX1 and 2 and are critical sites of heme degradation in healthy and diseased states. Here we review the functions of the macrophage heme oxygenase system and its clinical relevance in discrete groups of pathologies where heme has been demonstrated to play a driving role. HMOX1 function in macrophages is essential for limiting oxidative tissue damage in both acute and chronic hemolytic disorders. By degrading pro-inflammatory heme and releasing anti-inflammatory molecules such as carbon monoxide, HMOX1 fine-tunes the acute inflammatory response with consequences for disorders of hyperinflammation such as sepsis. We then discuss divergent beneficial and pathological roles for HMOX1 in disorders such as atherosclerosis and metabolic syndrome, where activation of the HMOX system sits at the crossroads of chronic low-grade inflammation and oxidative stress. Finally, we highlight the emerging role for HMOX1 in regulating macrophage cell death via the iron- and oxidation-dependent form of cell death, ferroptosis. In summary, the importance of heme clearance by macrophages is an active area of investigation with relevance for therapeutic intervention in a diverse array of human diseases.